2021
DOI: 10.3390/v13071244
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Longitudinal Evaluation of Six Commercial Immunoassays for the Detection of IgM and IgG Antibodies against SARS CoV-2

Abstract: The number of serological assays for SARS-CoV-2 has skyrocketed in the past year. Concerns have been raised regarding their performance characteristics, depending on the disease severity and the time of the analysis post-symptom onset (PSO). Thus, independent validations using an unbiased sample selection are required for meaningful serology data interpretation. We aimed to assess the clinical performance of six commercially available assays, the seroconversion, and the dynamics of the humoral response to SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…NS, nonsignificant, p > 0.05; *, p ≤ 0.05; **, p ≤ 0.01; ***, p ≤ 0.001; ****. p ≤ 0.0001.IgG antiS1/S2 (DiaSorin) when compared with other commercially available serological assays [9][10][11]. During the first visit, a weaker correlation between NT 50 and SARS-CoV-2 S1/S2 IgG (DiaSorin) was observed compared with previous reports 6.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…NS, nonsignificant, p > 0.05; *, p ≤ 0.05; **, p ≤ 0.01; ***, p ≤ 0.001; ****. p ≤ 0.0001.IgG antiS1/S2 (DiaSorin) when compared with other commercially available serological assays [9][10][11]. During the first visit, a weaker correlation between NT 50 and SARS-CoV-2 S1/S2 IgG (DiaSorin) was observed compared with previous reports 6.…”
mentioning
confidence: 66%
“…Serological assays are considered one of the most practical approaches for detecting antibodies, while correlations with neutralization assays may inform on infection protection correlates. Previous reports demonstrated the superior sensitivity and specificity for CLIA IgG antiS1/S2 (DiaSorin) when compared with other commercially available serological assays 9–11 …”
Section: Discussionmentioning
confidence: 99%
“…There is a downside to using IgG/IgM antibodies in regard to the significant variability in sensitivity of tests from different companies, yet they all provide good, high specificity [ 126 ]. Following BNT162b2 vaccination, it was suggested that adiponectin would be a better marker for predicting the immune responses to the vaccine [ 55 ].…”
Section: Resultsmentioning
confidence: 99%